Polyethylene copolymers for film layers

Multimodal medium density polyethylene (mMDPE) prepared by specific metallocene catalysts solves the problem of insufficient balance of mechanical properties and sealing properties in the prior art in membrane applications, and improves tensile modulus and drop The impact strength effect of darts while maintaining good optical performance.

CN119421907APending Publication Date: 2025-02-11北欧化工公司
View PDF 21 Cites 0 Cited by

Patent Information

Application Number
CN202380049006.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-23
Filing Date
2023-06-20
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

Existing multimodal medium density polyethylene (mMDPE) has a balance between mechanical properties and sealing properties in membrane applications, especially in terms of tensile modulus and dart impact strength, as well as haze and Processing challenges.

Method used

Multimodal medium density polyethylene (mMDPE) prepared with specific metallocene catalysts optimizes the polymer component design to improve the mechanical and sealing properties of the membrane by adjusting the density, melt flow rate and molecular weight distribution of the polymer. , while maintaining good optical performance.

Benefits of technology

Improved mechanical properties, especially tensile modulus and dart impact strength, maintain a good balance between mechanical properties and sealing properties, and improve the thermal viscosity and optical properties of the film, especially reduce haze .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005202333560000101
    Figure BDA0005202333560000101
  • Figure BDA0005202333560000111
    Figure BDA0005202333560000111
  • Figure BDA0005202333560000112
    Figure BDA0005202333560000112
Patent Text Reader

Abstract

The present invention relates to specific metallocene catalyzed multimodal medium density polyethylene (mMDPE), to the use of multimodal medium density polyethylene (mMDPE) in film applications and to films comprising the mMDPE of the invention.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention relates to metallocene-catalyzed multimodal medium density polyethylene (mMDPE), the use of multimodal medium density polyethylene (mMDPE) in film applications and films comprising the mMDPE of the invention.

[0002] State-of-the-art mLLDPE (metallocene-catalyzed linear low-density polyethylene) is widely used in daily life, such as packaging, due to its excellent cost-performance ratio.

[0003] Unimodal mLLDPE is typically used for film applications. Unimodal LLDPE has good optical properties, such as low haze, but melt processing of such polymers is not satisfactory, for example, from a production point of view and may also lead to quality problems in the final product. Multimodal mLLDPE with two or more different polymer components is easier to process, but melt homogenization of multimodal PE may be problematic, leading to inhomogeneous final products, such as high gel content in the final product.

[0004] Multimodal mLLDPE are known in the art.

[0005] WO 202100918, WO 2021009190 and WO 2021009191 of Borealis disclose a process for preparing a multimodal PE polymer in two loop reactors and a gas phase reactor in the presence of a silica-supported metallocene catalyst based on the metallocene complex bis(1-methyl-3-n-butylcyclopentadienyl)zirconium(IV) dichloride.

[0006] Film properties such as tensile modulus (TM) and impact strength (Dart Drop Impact, DDI) are not mentioned at all.

[0007] WO 2021009192 also discloses this method.

[0008] Again, there is no mention at all of the film properties such as tensile modulus (TM) and impact strength (Dart Drop Impact, DDI).

[0009] WO2008089978 discloses a multimodal medium density polyethylene polymer consisting of A) a lower molecular weight (LMW) polyethylene homopolymer component and B) a higher molecular weight (HMW) polyethylene copolymer component, the copolymer component being a copolymer of ethylene and at least one C3-12-alpha olefin, preferably 1-hexene.

[0010] The multimodal medium density polyethylene polymer of the inventive example is produced in the presence of a silica supported bis(n-butylcyclopentadienyl)dibenzyl hafnium catalyst in a loop reactor and a subsequent gas phase reactor and has a molecular weight of 930 kg / m 3%, a comonomer content of 2.13 mol% and having a Mw / Mn of 3.4. The film made from the multimodal medium density polyethylene polymer had a rather high haze value of about 52% measured on a 40 μm film.

[0011] There is a growing need to find multimodal PE polymers with different balances of properties to provide tailor-made solutions that meet the growing demands of end-use producers, such as reducing production costs while maintaining or even improving the properties of the final product. There is also a need for tailor-made polymer solutions to meet the requirements of evolving equipment technologies in the end-use areas.

[0012] Therefore, there is a need in the art to provide a material that provides good mechanical properties, particularly tensile modulus and / or dart impact strength (impact resistance), without compromising sealing performance and still has acceptable optical properties, i.e., a haze of less than 35% (for a 40 μm film).

[0013] The present inventors have now found that metallocene-catalyzed medium density polyethylene (mMDPE) prepared with a specific metallocene catalyst and having a specific polymer design produces films having improved mechanical properties, especially tensile modulus and dart impact strength (impact resistance), and an attractive balance between mechanical properties and sealing properties. In addition, such films show improved hot tack and optical properties, especially haze. Summary of the invention

[0014] Therefore, the present invention relates to a metallocene-catalyzed multimodal medium density polyethylene consisting of:

[0015] (i) 35.0 to 50.0 wt% of a polyethylene component (A) based on mMDPE, and

[0016] (ii) 50.0 to 65.0 wt% of a polyethylene component (B) based on mMDPE,

[0017] wherein the polyethylene polymer component (A) has

[0018] 950 to 975 kg / m 3 Density in the range (ISO 1183),

[0019] MFR2 in the range of 3.0 to 50.0 g / 10 min (190°C, 2.16 kg, ISO 1133);

[0020] The polyethylene component (B) has

[0021] 900 to 925 kg / m 3 Density in the range (ISO 1183),

[0022] MFR2 in the range of 0.001 to 1.0 g / 10 min (190°C, 2.16 kg, ISO 1133);

[0023] Among them, metallocene-catalyzed medium-density polyethylene (mMDPE) has

[0024] 920 to 945 kg / m 3 Density in the range (ISO 1183),

[0025] MFR2 (190°C, 2.16 kg, ISO 1133) in the range of 0.1 to 5.0 g / 10 min, and

[0026] MFR in the range of 27 to 40 21 Ratio of MFR (190℃, 21.6kg, ISO 1133) to MFR2 (190℃, 2.16kg, ISO1133) 21 / MFR2, and

[0027] Molecular weight distribution (MWD) Mw / Mn in the range of 4.2 to 10.0.

[0028] Surprisingly, such mMDPE provides films with improved mechanical properties, especially tensile modulus and / or dart drop impact strength (impact resistance), still with acceptable optical properties, i.e. haze below 35% (for 40 μm films) and an attractive balance between mechanical and sealing properties.

[0029] The present invention therefore further relates to a film comprising at least one layer comprising an mMDPE as described above.

[0030] definition

[0031] Where the term "comprising" is used in the present description and claims, it does not exclude other, not specifically stated, elements of major or minor functional importance. For the purposes of the present invention, the term "consisting of" is considered to be a preferred embodiment of the term "comprising". If a group is defined hereinafter as comprising at least a certain number of embodiments, this is also to be understood as disclosing the group, which preferably consists only of these embodiments.

[0032] Whenever the terms "including" or "having" are used, these terms are meant to be equivalent to "comprising" as defined above.

[0033] When an indefinite or definite article is used when referring to a singular noun, for example "a", "an" or "the", this includes a plural of that noun unless otherwise stated.

[0034] Metallocene-catalyzed medium density polyethylene (mMDPE) is defined in the present invention as a medium density polyethylene produced in the presence of a metallocene catalyst.

[0035] For the purposes of the present invention, "medium density polyethylene (MDPE) comprising a polyethylene component (A) and a polyethylene component (B)" means that the MDPE is produced in at least a two-step sequential polymerization process, wherein component (A) is produced first and then, in a subsequent polymerization step, component (B) is produced in the presence of component (A) to produce the MDPE, or vice versa, i.e. component (B) is produced first and then, in a subsequent polymerization step, component (A) is produced in the presence of component (B) to produce the MDPE.

[0036] MDPE produced in a multistage process is also known as an "in-situ" blend or a "reactor" blend. The resulting final product consists of an intimate mixture of polymers from two or more reactors whose different molecular weight distribution curves together form a molecular weight distribution curve with a broad maximum or two or more maxima, i.e., the final product is a multimodal polymer mixture.

[0037] In the context of medium density polyethylene (MDPE), the term "multimodal" refers herein to the multimodality of the melt flow rate (MFR) of at least two polyethylene components, i.e. the two polyethylene components have different MFR values. The multimodal medium density polyethylene may additionally or alternatively have multimodality between the two polyethylene components with respect to one or more other properties (such as density, comonomer type and / or comonomer content), which will be described below. DETAILED DESCRIPTION

[0038] Metallocene-catalyzed multimodal medium density polyethylene (mMDPE)

[0039] The metallocene-catalyzed multimodal mMDPE according to the present invention has a molecular weight of 920 to 945 kg / m 3 , preferably 922 to 940 kg / m 3 , more preferably 923 to 935 kg / m 3 Density within the range (ISO 1183).

[0040] The MFR2 (190°C, 2.16 kg, ISO 1133) of the metallocene-catalyzed mMDPE is in the range of 0.1 to 5.0 g / 10 min, preferably 0.2 to 3.0 g / 10 min, more preferably 0.3 to 2.5 g / 10 min, even more preferably 0.4 to 2.0 g / 10 min.

[0041] MFR of metallocene-catalyzed mMDPE 21(190°C, 21.6 kg, ISO 1133) may be in the range of 8.0 to 60.0 g / 10 min, preferably in the range of 10.0 to 55.0 g / 10 min, more preferably in the range of 12.0 to 50.0 g / 10 min, and most preferably in the range of 15.0 to 45.0 g / 10 min.

[0042] The metallocene-catalyzed mMDPE according to the present invention also has an MFR in the range of 27.0 to 40.0, preferably 28.0 to 38.0, more preferably 29.0 to 35.0. 21 / MFR2 flow rate ratio (FRR).

[0043] In one embodiment of the present invention, the mMDPE has one or two or all of the following:

[0044] 922 to 940 kg / m 3 , preferably 923 to 935 kg / m 3 Density within the range (ISO1183),

[0045] MFR2 (190°C, 2.16 kg, ISO 1133) in the range of 0.2 to 3.0 g / 10 min, preferably 0.3 to 2.5 g / 10 min, more preferably 0.4 to 2.0 g / 10 min,

[0046] MFR in the range of 10.0 to 55.0 g / 10 min, preferably in the range of 12.0 to 50.0 g / 10 min, more preferably in the range of 15.0 to 45.0 g / 10 min 21 (190°C, 21.6kg, ISO 1133), and / or

[0047] Flow rate ratio (FRR) MFR in the range of 28.0 to 38.0, preferably 29.0 to 35.0 21 / MFR2.

[0048] Furthermore, the metallocene-catalyzed mMDPE has a molecular weight distribution (MWD) in the range of 4.2 to 10.0, preferably 4.5 to 8.0, more preferably 4.8 to 6.5.

[0049] Furthermore, the metallocene-catalyzed mMDPE according to the present invention may have a weight average molecular weight Mw of at least 60,000 g / mol, preferably in the range of 70,000 to 130,000 g / mol, more preferably 75,000 to 125,000 g / mol, still more preferably 80,000 to 120,000 g / mol.

[0050] The metallocene-catalyzed mMDPE according to the present invention may have a melting temperature Tm (measured with DSC) of at least 125°C, preferably in the range of 125 to 135°C.

[0051] Metallocene-catalyzed mMDPE consists of:

[0052] (i) 35.0 to 50.0 wt%, preferably 38.0 to 48.0 wt%, relative to the total weight of mMDPE, of a polyethylene component (A) having a molecular weight of 950 to 975 kg / m 3 A density in the range of 1.5 to 2.0 g / 10 min and an MFR2 (190°C, 2.16 kg, ISO 1133) of 3.0 to 50 g / 10 min; and

[0053] (ii) 50.0 to 65.0 wt%, preferably 52.0 to 62.0 wt%, relative to the total weight of mMDPE, of a polyethylene component (B) having a molecular weight of 900 to 925 kg / m 3 The invention relates to a polymer having a density in the range of 0.001 to 1.0 g / 10 min and a MFR2 (190°C, 2.16 kg, ISO 1133) of 0.001 to 1.0 g / 10 min.

[0054] The amounts of components (A) and (B) add up to 100 wt%.

[0055] According to the present invention, the polyethylene component (A) is a polyethylene homopolymer.

[0056] For the purposes of the present invention, a polyethylene homopolymer is a polymer comprising at least 99.0 wt%, in particular at least 99.5 wt% of ethylene monomer units. Thus, a polyethylene homopolymer may contain up to 1.0 wt%, but preferably only up to 0.5 wt%, for example up to 0.2 wt% or even only up to 0.1 wt% of comonomer units.

[0057] In one embodiment of the present invention, the amount of comonomer in the polyethylene homopolymer component is 13 C-NMR was undetectable.

[0058] The polyethylene component (B) is a copolymer of ethylene and a C4 to C8 comonomer, preferably a C4 to C6 comonomer, more preferably a copolymer of ethylene and 1-hexene.

[0059] Preferably, polyethylene component (B) consists of a single ethylene copolymer and polyethylene component (A) may consist of a single ethylene homopolymer, or polyethylene component (A) may be an ethylene homopolymer mixture comprising (e.g., consisting of) a first ethylene polymer fraction (A-1) and a second ethylene polymer fraction (A-2), wherein both fractions are homopolymers. Polyethylene component (A) may be unimodal or multimodal.

[0060] In an embodiment of the present invention the polyethylene component (A) is preferably unimodal and consists of a single ethylene homopolymer.

[0061] The total amount of comonomers (i.e. C4 to C8 comonomers, preferably C4 to C6, more preferably 1-hexene) in the metallocene-catalyzed mMDPE is preferably in the range of 1.5 to 5.0 mol%, more preferably 1.6 to 4.0 mol%, even more preferably 1.7 to 3.5 mol%, still more preferably 1.8 to 3.0 mol%.

[0062] The total amount of comonomers (i.e. C4 to C8 comonomers, preferably C4 to C6, more preferably 1-hexene) in the polyethylene component (B) is preferably in the range of 2.0 to 8.0 mol%, more preferably 2.5 to 7.0 mol%, even more preferably 3.0 to 6.0 mol%, and still more preferably 3.2 to 5.5 mol%.

[0063] The MFR2 of polyethylene component (A) is preferably in the range of 4.0 to 30.0 g / 10min, more preferably 5.0 to 20.0 g / 10min, even more preferably 6.0 to 15.0 g / 10min, most preferably 6.5 to 12.0 g / 10min, such as 7.0 to 10.0 g / 10min.

[0064] The density of the polyethylene component (A) is preferably in the range of 955 to 972 kg / m 3 , more preferably 960 to 970 kg / m 3 , even more preferably 962 to 968 kg / m 3 within the range.

[0065] In another embodiment, the polyethylene component (A) consists of two fractions, namely a first ethylene polymer fraction (A-1) and a second ethylene polymer fraction (A-2), preferably consists of a first ethylene homopolymer fraction (A-1) and a second ethylene homopolymer fraction (A-2).

[0066] It is possible to produce fraction (A-1) first and then, in a subsequent reactor, produce fraction (A-2) in the presence of fraction (A-1), or vice versa, i.e., produce fraction (A-2) first and then, in a subsequent reactor, produce fraction (A-1) in the presence of fraction (A-2). Preferably, fraction (A-1) is produced first.

[0067] The MFR2 and / or density of fractions (A-1) and (A-2) may be the same or may be different from each other.

[0068] The MFR2 of the polyethylene component (B) is preferably in the range of 0.005 to 0.8 g / 10 min, more preferably 0.01 to 0.6 g / 10 min, even more preferably 0.05 to 0.5 g / 10 min.

[0069] The density of the polyethylene component (B) is preferably in the range of 903 to 920 kg / m 3 , more preferably 905 to 915 kg / m 3 , even more preferably 905 to 912 kg / m 3 within the range.

[0070] Metallocene-catalyzed mMDPE can be produced by polymerizing with a metallocene catalyst system using conditions that produce a multimodal (eg, bimodal) polymer product.

[0071] Thus, the metallocene-catalyzed mMDPE can be produced in a two-stage process, preferably comprising a slurry reactor (e.g. a loop reactor), wherein the slurry (e.g. a loop) reactor is connected in series with a gas phase reactor (GPR), whereby the polyethylene component (A) or the polyethylene component (B) is produced in the slurry reactor, and then the other ethylene polymer component is produced in the GPR in the presence of the first produced ethylene polymer component to produce the metallocene-catalyzed mMDPE, preferably, the polyethylene component (A) is produced in the slurry reactor and the polyethylene component (B) is produced in the GPR in the presence of the polyethylene component (A) to produce the metallocene-catalyzed mMDPE.

[0072] In case the polyethylene component (A) of the metallocene-catalyzed mMDPE consists of ethylene polymer fractions (A-1) and (A-2), the metallocene-catalyzed mMDPE may be produced in a three-stage process, which preferably comprises a first slurry reactor (loop reactor 1), wherein the first slurry (loop) reactor is connected in series with a further slurry reactor (loop reactor 2), such that the first ethylene polymer fraction (A-1) produced in slurry reactor 1 is fed to slurry reactor 2, where the second ethylene polymer fraction (A-2) is produced in the presence of the first fraction (A-1). Fraction (A-1) may be produced first and then, in a subsequent reactor, fraction (A-2) is produced in the presence of fraction (A-1), or vice versa, i.e., fraction (A-2) is produced first and then, in a subsequent reactor, fraction (A-1) is produced in the presence of fraction (A-2). Preferably, fraction (A-1) is produced first.

[0073] Within the scope of the present invention, the first and second ethylene polymer parts (A-1 and A-2) of the polyethylene component (A) are present in a weight ratio of 4:1 to 1:4, for example 3:1 to 1:3, or 2:1 to 1:2, or 1:1, based on the total weight of the polyethylene component (A).

[0074] The first and optional second polymerisation stages are preferably slurry polymerisation steps.

[0075] Slurry polymerization is usually carried out in an inert diluent, which is usually a hydrocarbon diluent, such as methane, ethane, propane, n-butane, isobutane, pentane, hexane, heptane, octane, etc., or a mixture thereof. Preferably, the diluent is a low boiling hydrocarbon having 1 to 4 carbon atoms or a mixture of these hydrocarbons. A particularly preferred diluent is propane, which may contain small amounts of methane, ethane and / or butane.

[0076] The temperature in each of the first and optional second polymerization stages is generally from 60 to 100° C., preferably from 70 to 90° C. Excessively high temperatures should be avoided to prevent partial dissolution of the polymer into the diluent and contamination of the reactor. The pressure is from 1 to 150 bar, preferably from 40 to 80 bar.

[0077] Slurry polymerization can be carried out in any known reactor for slurry polymerization. Such reactors include continuous stirred tank reactors or autoclave reactors and loop reactors. In one embodiment, slurry polymerization is particularly preferably carried out in a loop reactor. In such a reactor, the slurry is circulated at high speed along a closed pipeline by using a circulating pump. Loop reactors are well known in the art, and examples are given, for example, in US-A-4582816, US-A-3405109, US-A-3324093, EP-A-479186 and US-A-5391654. Therefore, it is preferred to carry out the first and second polymerization stages in the form of slurry polymerization in two continuous loop reactors.

[0078] The slurry can be taken out from each reactor continuously or intermittently. The preferred mode of intermittent taking out is to use settling legs, wherein the slurry is concentrated and then a batch of concentrated slurry is taken out from the reactor. The use of settling legs is disclosed in US-A-3374211, US-A-3242150 and EP-A-1310295. Continuous taking out is disclosed in EP-A-891990, EP-A-1415999, EP-A-1591460 and WO-A-2007 / 025640. As disclosed in EP-A-1310295 and EP-A-1591460, continuous taking out is advantageously combined with a suitable concentration method. In one embodiment, preferably slurry is taken out continuously from each of the first and optional second polymerization stage.

[0079] Hydrogen is usually introduced into the first and optional second polymerization stage for controlling the MFR2 of the ethylene polymer. The amount of hydrogen required to achieve the desired MFR depends on the catalyst used and the polymerization conditions.

[0080] Hence, the slurry reactor is preferably connected in series to a gas phase reactor (GPR) such that the polyethylene component (A) leaving the slurry reactor is fed to the GPR to produce the multimodal polyethylene copolymer.

[0081] The last polymerization stage is a gas phase polymerization step, ie carried out in a gas phase reactor. Any suitable gas phase reactor known in the art may be used, such as a fluidized bed gas phase reactor.

[0082] For gas phase reactors, the reaction temperature used is usually 60-115° C. (e.g. 70-110° C.), the reactor pressure is usually in the range of 10-25 bar, and the residence time is usually 1-8 hours. The gas used is usually a non-reactive gas, such as nitrogen or a low boiling hydrocarbon, such as propane and a monomer (e.g. ethylene).

[0083] A chain transfer agent, such as hydrogen, is usually added to this polymerization stage.

[0084] Such processes are described inter alia in WO 2016 / 198273, WO 2021009189, WO 2021009190, WO 2021009191 and WO 2021009192. Full details of how to prepare suitable multimodal polymers can be found in these references.

[0085] A suitable process is the Borstar PE process or the Borstar PE 3G process.

[0086] Therefore, the metallocene-catalyzed mMDPE according to the present invention is preferably produced in a slurry-gas phase cascade or a slurry-slurry-gas phase cascade. Such a polymerization step may be preceded by a prepolymerization step.

[0087] The purpose of prepolymerization is to polymerize a small amount of polymer onto the catalyst at low temperature and / or low monomer concentration. By prepolymerization, the performance of the catalyst in slurry can be improved and / or the properties of the final polymer can be changed. The prepolymerization step is preferably carried out in slurry. Therefore, the prepolymerization step can be carried out in a loop reactor.

[0088] Then, the prepolymerization is preferably carried out in an inert diluent, which is generally a hydrocarbon diluent, such as methane, ethane, propane, n-butane, isobutane, pentane, hexane, heptane, octane, etc., or a mixture thereof. Preferably, the diluent is a low-boiling hydrocarbon having 1 to 4 carbon atoms or a mixture of these hydrocarbons.

[0089] The temperature in the prepolymerization step is usually from 0 to 90°C, preferably from 20 to 80°C, more preferably from 45 to 75°C.

[0090] The pressure is not critical and is generally 1 to 150 bar, preferably 40 to 80 bar.

[0091] The amount of monomer is usually such that 0.1 to 1000 grams of monomer are polymerized per gram of solid catalyst component in the prepolymerization step. As known to those skilled in the art, the catalyst particles recovered from the continuous prepolymerization reactor do not all contain the same amount of prepolymer. On the contrary, each particle has its own characteristic amount, which depends on the residence time of the particle in the prepolymerization reactor. Because some particles stay in the reactor for a relatively long time, and some stay for a relatively short time, the amount of prepolymer on different particles is also different, and some single particles may contain the amount of prepolymer beyond the above range. However, the average amount of prepolymer on the catalyst is usually within the above range.

[0092] As is known in the art, the molecular weight of the prepolymer can be controlled by hydrogen.In addition, antistatic additives can be used to prevent the particles from sticking to each other or to the reactor walls, as disclosed in WO-A-96 / 19503 and WO-A-96 / 32420.

[0093] When there is a prepolymerization step, the catalyst components are preferably all introduced into the prepolymerization step. However, when the solid catalyst component and the cocatalyst can be fed separately, it is possible that only a part of the cocatalyst is introduced into the prepolymerization stage, while the rest is introduced into the subsequent polymerization stage. Moreover, in this case, it is necessary to introduce so much cocatalyst into the prepolymerization stage in order to obtain a sufficient polymerization reaction therein.

[0094] It is to be understood that within the scope of the present invention the amount of polymer produced in the prepolymerisation is within 1.0 to 5.0 wt% relative to the final metallocene catalysed mMDPE. This can be counted as part of the first polyethylene component (A).

[0095] catalyst

[0096] The metallocene-catalyzed mMDPE of the present invention is mMDPE prepared using a metallocene catalyst. The metallocene catalyst comprises a metallocene complex and a cocatalyst. The metallocene compound or complex is also referred to herein as an organometallic compound (C).

[0097] The organometallic compound (C) comprises a transition metal (M) from Groups 3 to 10 of the Periodic Table of Elements (IUPAC 2007) or from the actinides or lanthanides.

[0098] According to the present invention, the term "organometallic compound (C)" includes any metallocene or non-metallocene compound of a transition metal, which carries at least one organic (coordinating) ligand and exhibits catalytic activity alone or together with a cocatalyst. Transition metal compounds are well known in the art, and the present invention encompasses compounds of metals from Groups 3 to 10, e.g. Groups 3 to 7, or Groups 3 to 6, e.g. Groups 4 to 6, of the Periodic Table (IUPAC 2007), as well as lanthanides or actinides.

[0099] In one embodiment, the organometallic compound (C) has the following formula (I):

[0100]

[0101] Wherein each X is independently a halogen atom, C 1-6 -alkyl, C 1-6 - alkoxy, phenyl or benzyl;

[0102] Each Het is independently a monocyclic heteroaromatic group containing at least one heteroatom selected from O or S;

[0103] L is -R'2Si-, wherein each R' is independently a C substituted with an alkoxy group having 1 to 10 carbon atoms. 1-20 -Hydrocarbon or C 1-10 -alkyl;

[0104] M is Ti, Zr or Hf;

[0105] Each R 1 Same or different, is C 1-6 -alkyl or C 1-6 - alkoxy;

[0106] Each n is 1 to 2;

[0107] Each R 2 Same or different, is C 1-6 -alkyl, C 1-6 -alkoxy or -Si(R)3 group;

[0108] Each R is optionally replaced by 1 to 3 C 1-6 -alkyl substituted C 1-10 -alkyl or phenyl; and each p is 0 to 1.

[0109] Preferably, the compound of formula (I) has the structure

[0110]

[0111] Wherein each X is independently a halogen atom, C 1-6 -alkyl, C 1-6-alkoxy, phenyl or benzyl; L is Me2Si-;

[0112] Each R 1 Same or different and C 1-6 - alkyl, for example methyl or tert-butyl;

[0113] Each n is 1 to 2;

[0114] R 2 is -Si(R)3alkyl; each p is 1;

[0115] Each R is C 1-6 -alkyl or phenyl.

[0116] Highly preferred complexes of formula (I) are

[0117]

[0118]

[0119] Most preferably, the complex dimethylsilanediylbis[2-(5-trimethylsilylfuran-2-yl)-4,5-dimethylcyclopentadien-1-yl]zirconium dichloride is used.

[0120] More preferably, the polyethylene components (A) and (B) of the metallocene-catalyzed mMDPE are prepared using the same metallocene catalyst, ie in the presence of the same metallocene catalyst.

[0121] To form the catalyst, a cocatalyst, also called an activator, well known in the art is used. Cocatalysts containing Al or B are well known and can be used here. Preferably, an aluminoxane (such as MAO) or a boron-based cocatalyst (such as a borate) is used.

[0122] In contrast to Ziegler Natta catalysis, polyethylene copolymers made using single-site catalysis have characteristics that distinguish them from Ziegler Natta materials. In particular, the comonomer distribution is more uniform. This can be shown using TREF or Crystaf techniques. Catalyst residues can also be indicative of the catalyst used. For example, Ziegler Natta catalysts do not contain Zr or Hf Group (IV) metals.

[0123] The metallocene-catalyzed mMDPE may contain additives and / or fillers.

[0124] Optional additives and fillers and the amounts used are conventional in the field of film applications. Examples of such additives are, inter alia, antioxidants, processing stabilizers, UV stabilizers, pigments, fillers, antistatic additives, antiblocking agents, nucleating agents, acid scavengers and polymer processing aids (PPAs).

[0125] As mentioned above, the metallocene-catalyzed mMDPE according to the present invention provides improved mechanical properties, especially tensile modulus and dart drop impact strength (impact strength) and additionally an attractive balance between mechanical properties and sealing properties.

[0126] The present invention therefore further relates to a film comprising at least one layer comprising a metallocene-catalyzed mMDPE as described above.

[0127] membrane

[0128] The film of the present invention comprises at least one metallocene-catalyzed mMDPE as defined above. The film may be a monolayer film comprising the polyethylene composition defined above or a multilayer film wherein at least one layer comprises the polyethylene composition defined above. The terms "monolayer film" and "multilayer film" have well-known meanings in the art.

[0129] Preferably, at least one layer of the present invention comprises at least 50 wt%, more preferably at least 60 wt%, even more preferably at least 70 wt%, yet more preferably at least 80 wt% of the metallocene-catalyzed mMDPE of the present invention, based on the total weight of the film. Most preferably, the at least one layer of the film of the present invention consists of metallocene-catalyzed mMDPE.

[0130] The film is preferably produced by any conventional film extrusion process known in the art, including cast film and blown film extrusion. Most preferably, the film is a blown film or cast film, especially a blown film. For example, blown film is produced by extruding through an annular die and blowing into a tubular film by forming bubbles, which burst between rollers after solidification. The film can then be cut, cut or converted (e.g., folded) as required. Traditional film production techniques can be used in this regard. If preferred blown film or cast film is a multilayer film, each layer is typically coextruded. The technician will know suitable extrusion conditions.

[0131] The film according to the present invention may be subjected to post-treatment processes such as surface modification, lamination or orientation processes, etc. Such orientation processes may be uniaxial (MDO) or biaxial orientation, wherein uniaxial orientation is preferred.

[0132] In another preferred embodiment, the film is non-oriented.

[0133] Preferred films according to the invention are monolayer blown films.

[0134] The thickness of the single-layer film of the present invention may be 20 to 120 μm, preferably 30 to 100 μm, and more preferably 35 to 80 μm.

[0135] Films based on the metallocene-catalyzed mMDPE defined above lead to improved mechanical properties (higher stiffness (DDI) at the same dart impact strength or higher dart impact strength (DDI) at the same stiffness compared to the comparative examples) without deteriorating the sealing properties and still having acceptable optical properties, especially haze.

[0136] Therefore, in one embodiment, the film according to the invention

[0137] a) a tensile modulus (measured on a 40 μm monolayer test blown film according to ISO 527-3) in the machine direction (MD) in the range of 350 MPa to 800 MPa, preferably 380 MPa to 800 MPa and in the transverse direction (TD) in the range of 400 MPa to 800 MPa, preferably 420 MPa to 800 MPa, and

[0138] b) a dart drop impact strength (DDI) of at least 150 g to at most 500 g, preferably 200 g to at most 450 g, more preferably 220 g to at most 400 g, measured on a 40 μm single layer test blown film according to ISO 7765-1:1988, and

[0139] c) according to formula (I):

[0140] Relationship between mechanical properties and sealing properties determined on 40 μm test blown films, wherein the tensile modulus in the longitudinal direction is measured on 40 μm test blown films at 23°C according to ISO 527-3, DDI is the dart impact strength determined on 40 μm test blown films according to ISO 7765-1:1988, and SIT is the seal initiation temperature measured on 40 μm test blown films as described in the experimental part.

[0141] Preferably, the TM(MD) of this embodiment * DDI / SIT>700, more preferably>750.

[0142] TM(MD) of this embodiment * The suitable upper limit of DDI / SIT is 1500, preferably 1000, more preferably 900.

[0143] In another embodiment, the membrane according to the present invention

[0144] a) a tensile modulus (measured on a 40 μm monolayer test blown film according to ISO 527-3) in the machine direction (MD) in the range of 200 MPa to 600 MPa, preferably 250 MPa to 400 MPa and in the transverse direction (TD) in the range of 250 MPa to 800 MPa, preferably 300 MPa to 500 MPa, and

[0145] b) a dart drop impact strength (DDI) of at least 700 g to at most 2000 g, preferably 800 g to at most 1600 g, more preferably 900 g, measured on a 40 μm single-layer test blown film according to ISO 7765-1:1988;

[0146] g to a maximum of 1400 g, and

[0147] c) according to formula (I):

[0148] The improved relationship between the mechanical properties and the sealing properties determined on a 40 μm test blown film is shown in Figure 2, wherein the tensile modulus in the longitudinal direction is measured on a 40 μm test blown film at 23°C according to ISO 527-3, DDI is the dart impact strength determined on a 40 μm test blown film according to ISO 7765-1:1988, and SIT is the seal initiation temperature measured on a 40 μm test blown film as described in the experimental part.

[0149] Preferably, the TM(MD) of this embodiment * DDI / SIT>2000, more preferably>2500.

[0150] TM(MD) of this embodiment * The suitable upper limit of DDI / SIT is 5,000, preferably 4,500, more preferably 4,000.

[0151] The haze measured according to ASTM D1003 on a 40 μm test blown film for both embodiments is below 35%, preferably in the range of 5% to 32%, more preferably in the range of 10% to 30%, such as 10% to 20% or 21% to 30%.

[0152] The relative Elmendorf tear resistance of the films according to both embodiments of the invention measured according to ISO 6383 / 2 on a blown film with a film thickness of 40 μm may be at least 60 N / mm to at most 300 N / mm, preferably 70 N / mm to at most 250 N / mm, more preferably 80 N / mm to at most 220 N / mm in the machine direction (MD), and

[0153] In the transverse direction (TD) it is at least 140 N / mm to at most 350 N / mm, preferably 150 N / mm to at most 300 N / mm, more preferably 170 N / mm to at most 250 N / mm.

[0154] The films according to the invention are very suitable for use in a variety of packaging applications.

[0155] Furthermore, the film according to the invention can be used as a layer in a multilayer polyethylene-based blown film, preferably as a core layer in a multilayer polyethylene-based blown film.

[0156] The present invention will be further described with reference to the following non-limiting examples.

[0157] Determination method

[0158] Unless otherwise stated in the description or the experimental section, the following methods were used to determine the properties of the polymers (including parts and components thereof) and / or any sample preparations thereof as described in the text or in the experimental section.

[0159] Melt flow rate:

[0160] The melt flow rate (MFR) is determined according to ISO 1133 and is expressed in g / 10 min. The MFR is an indicator of the flowability of the polymer and therefore of its processability. The MFR of polyethylene is determined at 190°C. The MFR can be determined at different loads, for example 2.16 kg (MFR2), 5 kg (MFR5) or 21.6 kg (MFR 21 ).

[0161] Calculation of MFR2 of component (B)

[0162] logA=x·logB+(1-x)·logC

[0163]

[0164] For component B:

[0165] B = MFR2 of component (A)

[0166] C = MFR2 of component (B)

[0167] A = Final MFR2 of multimodal mMDPE (blend)

[0168] X = weight fraction of component (A).

[0169] density

[0170] The density of polymers is measured according to ISO 1183 and is expressed in kg / m 3 Given, the sample preparation was carried out according to ISO 1872-2.

[0171] GPC

[0172] The average molecular weight (M z 、M w and M n), molecular weight distribution (MWD) and its breadth described by the polydispersity index PDI = Mw / Mn (where Mn is the number average molecular weight and Mw is the weight average molecular weight) are calculated by gel permeation chromatography (GPC) using the following formula:

[0173]

[0174] For a constant elution volume interval ΔV i , where A i and M i and elution volume V i The associated chromatographic peak slice area and the polyolefin molecular weight (MW), where N equals the number of data points obtained from the chromatogram between the integration limits.

[0175] A high temperature GPC instrument equipped with an infrared (IR) detector (IR4 or IR5 from PolymerChar (Valencia, Spain)) and equipped with 3x Agilent-PLgel Olexis and 1x Agilent-PLgel Olexis Guard columns was used. 1,2,4-Trichlorobenzene (TCB) stabilized with 250 mg / L 2,6-di-tert-butyl-4-methylphenol was used as solvent and mobile phase. The chromatographic system was operated at a constant flow rate of 1 mL / min at 160°C. 200 μL of sample solution was injected for each analysis. Data collection was performed using Agilent Cirrus software version 3.3 or PolymerChar GPC-IR control software.

[0176] The column set was calibrated using universal calibration (according to ISO 16014-2:2003) with 19 narrow MWD polystyrene (PS) standards ranging from 0.5 kg / mol to 11500 kg / mol. The PS standards were dissolved at room temperature for several hours. The conversion of polystyrene peak molecular weight to polyolefin molecular weight was accomplished by using the Mark Houwink equation and the following Mark Houwink constants:

[0177] K PS =19x10 -3 mL / g, α PS =0.655

[0178] K PE =39x10 -3 mL / g, α PE =0.725

[0179] K PP =19x10 -3 mL / g, α PP =0.725

[0180] A third-order polynomial fit was used to fit the calibration data.

[0181] All samples were prepared in the concentration range of 0.5-1 mg / ml and dissolved at 160°C for 2.5 hours for PP or 3 hours for PE with continuous gentle shaking.

[0182] To exclude the influence of additives such as irganox 1010, irgafos 168 or some other low molecular weight oligomers, the low molecular weight integration limit was set at the valley between the antioxidant peak and the polymer peak (logM of the analyzed sample was about 2.8 (PE equivalent)).

[0183] Comonomer content:

[0184] Quantification of microstructure by NMR spectroscopy

[0185] Quantitative nuclear magnetic resonance (NMR) spectroscopy was used to quantify the comonomer content of the polymers.

[0186] A Bruker Avance III 400 MHz NMR spectrometer was used to analyze the 1 H and 13 C was operated at 500.13 and 125.76 MHz and quantitative data were recorded in the molten state. 13 C{ 1 H}NMR spectra. All spectra were obtained using 13 The spectra were recorded at 150 °C using a C-optimized 7 mm magic angle spinning (MAS) probe head with nitrogen used for all pneumatics. Approximately 200 mg of material was loaded into a 7 mm outer diameter zirconium oxide MAS rotor and spun at 4 kHz. This setup was chosen primarily for the high sensitivity required for rapid identification and accurate quantification {klimke06, parkinson07, castignolles09}. Standard single pulse excitation was used, utilizing NOE {pollard04, klimke06} with a short recycle delay of 3 s and an RS-HEPT decoupling scheme {fillip05, griffin07}. A total of 1024 (1k) transients were acquired for each spectrum.

[0187] Quantitative 13 C{ 1 H} NMR spectra were processed, integrated, and the relevant quantitative properties were determined from the integration. All chemical shifts were internally referenced to the bulk methylene signal (δ+) at 30.00 ppm.

[0188] The amount of ethylene is quantified using the integration of the methylene (δ+) sites at 30.00 ppm and taking into account the number of reported sites per monomer:

[0189] E=I δ+ / 2

[0190] Correction for the presence of isolated comonomer units is based on the number of isolated comonomer units present:

[0191] E total = E + (3 * B+2 * H) / 2

[0192] where B and H are defined for their respective comonomers. Corrections are made in a similar manner when there is continuous and discontinuous comonomer incorporation.

[0193] Characteristic signals corresponding to the incorporation of 1-butene were observed and the comonomer fraction was calculated as the fraction of 1-butene in the polymer relative to all monomers in the polymer:

[0194] fB total = (B total / (E total + B total + H total)

[0195] Use 39.8ppm * The amount of isolated 1-butene incorporated into the EEBEE sequence was quantified by integrating the B2 sites and taking into account the number of reporter sites per comonomer:

[0196] B=I *B2

[0197] If present, the amount of continuously incorporated 1-butene in the EEBBEE sequence was quantified using the integration of the ααB2B2 site at 39.4 ppm and taking into account the number of reported sites for each comonomer:

[0198] BB=2 * IααB2B2

[0199] If present, the amount of non-continuous incorporation of 1-butene in the EEBEBEE sequence was quantified using the integration of the ββB2B2 site at 24.6 ppm and taking into account the number of reporting sites per comonomer:

[0200] BEB=2 * IββB2B2

[0201] Due to the isolated (EEBEE) and discontinuously incorporated (EEBEBEE) 1-butene * B2 and * The βB2B2 sites were overlapped separately and the total amount of isolated 1-butene incorporation was corrected based on the amount of discontinuous 1-butene present:

[0202] B=I *B2 -2 * I ββB2B2

[0203] No BBB sequence was observed. The total 1-butene content was calculated based on the sum of isolated, continuously and discontinuously incorporated 1-butene:

[0204] Total B = B + BB + BEB

[0205] The total mole fraction of 1-butene in the polymer is then calculated as:

[0206] fB=B total / (E total+B total+H total)

[0207] A characteristic signal corresponding to the incorporation of 1-hexene was observed and the comonomer fraction was calculated as the fraction of 1-hexene in the polymer relative to all monomers in the polymer:

[0208] fH total = H total / (E total + B total + H total)

[0209] Use 38.3ppm * The amount of isolated 1-hexene incorporated into the EEHEE sequence was quantified by integrating the B4 sites and taking into account the number of reporter sites per comonomer:

[0210] H=I *B4

[0211] If present, the amount of continuously incorporated 1-hexene in the EEHHEE sequence was quantified using the integration of the ααB4B4 site at 40.5 ppm and taking into account the number of reporter sites for each comonomer:

[0212] HH=2 * IααB4B4

[0213] If present, the amount of non-continuous incorporation of 1-hexene in the EEHEHEE sequence was quantified using the integration of the ββB4B4 site at 24.7 ppm and taking into account the number of reporter sites per comonomer:

[0214] HEH=2 * IββB4B4

[0215] No HHH sequence was observed. The total 1-hexene content was calculated based on the sum of isolated, continuous and discontinuously incorporated 1-hexene:

[0216] Total H = H + HH + HEH

[0217] The total mole fraction of 1-hexene in the polymer was then calculated as:

[0218] fH=H total / (E total+B total+H total)

[0219] The mole percentage of comonomer incorporation is calculated from the mole fraction:

[0220] B [mol%] = 100 * f

[0221] H [mol%] = 100 * f

[0222] The weight percent of comonomer incorporation is calculated from the mole fraction:

[0223] B [wt%] = 100 * (fB * 56.11) / ((fB * 56.11)+(fH * 84.16)+((1-(fB+fH)) * 28.05))

[0224] H [wt%] = 100 * (fH * 84.16) / ((fB * 56.11)+(fH * 84.16)+((1-(fB+fH)) * 28.05))

[0225] References:

[0226] Klimke, K., Parkinson, M., Piel, C., Kaminsky, W., Spiess, HW, Wilhelm, M., Macromol. Chem. Phys. 2006; 207:382.

[0227] Parkinson, M., Klimke, K., Spiess, HW, Wilhelm, M., Macromol. Chem. Phys. 2007; 208:2128.

[0228] Pollard,M.,Klimke,K.,Graf,R.,Spiess,HW,Wilhelm,M.,Sperber,O.,Piel,C.,Kaminsky,W.,Macromolecules 2004;37:813.

[0229] Filip,X.,Tripon,C.,Filip,C.,J.Mag.Resn.2005,176,239.

[0230] Griffin,JM,Tripon,C.,Samoson,A.,Filip,C.,and Brown,SP,Mag.Res.inChem.2007 45,S1,S198.

[0231] Castignolles,P.,Graf,R.,Parkinson,M.,Wilhelm,M.,Gaborieau,M.,Polymer50(2009)2373

[0232] Busico,V.,Cipullo,R.,Prog.Polym.Sci.26(2001)443.

[0233] Busico,V.,Cipullo,R.,Monaco,G.,Vacatello,M.,Segre,AL,Macromoleucles30(1997)6251.

[0234] Zhou,Z.,Kuemmerle,R.,Qiu,X.,Redwine,D.,Cong,R.,Taha,A.,Baugh,D.Winniford,B.,J.Mag.Reson.187(2007)225.

[0235] Busico,V.,Carbonniere,P.,Cipullo,R.,Pellecchia,R.,Severn,J.,Talarico,G.,Macromol.Rapid Commun.2007,28,1128.

[0236] Resconi, L., Cavallo, L., Fait, A., Piemontesi, F., Chem. Rev. 2000, 100, 1253. DSC analysis, melting (Tm)

[0237] Data can be measured with a TA Instruments Q2000 Differential Scanning Calorimetry (DSC) on 5 to 7 mg samples. The DSC is run according to ISO 11357 / Part 3 / Method C2 in the temperature range of -30 to +225°C with a scan rate of 10°C / min in a hot / cold / hot cycle.

[0238] The crystallization temperature (Tm) and the crystallization enthalpy (Hc) are determined by the cooling step, while the melting temperature (Tm) and the melting enthalpy (Hm) are determined by the second heating step.

[0239] Dart Drop Intensity (DDI): Determination of impact resistance by free falling dart method

[0240] DDI was measured according to ISO 7765-1:1988 / Method A on films (non-oriented films and laminates) produced as shown below. This test method covers the determination of the energy that will cause film failure under specified conditions of impact with a dart falling freely from a specified height, which will cause 50% of the test specimens to fail (Step Method A). A uniform increment of the missile mass was used during the test, and after each specimen test, the missile weight was reduced or increased by a uniform increment depending on the observed result (failure or no failure) of the specimen.

[0241] Standard conditions:

[0242] Adjustment time: >96h at 50±2℃±10%rh

[0243] Test temperature: 23℃

[0244] Dart head material: phenolic resin

[0245] Dart diameter: 38mm

[0246] Drop height: 660mm

[0247] result:

[0248] Impact failure weight - 50% [g]

[0249] Tensile modulus

[0250] The tensile tests were carried out according to ISO 527-3, and in addition the modulus of elasticity (secant modulus between 0.05% and 0.25% elongation) was determined. Type 2 (parallel-sided specimens) specimens were used.

[0251] During the test, the specimen is extended along its long axis and the tensile properties are determined at a constant test speed (crosshead speed) until the specimen breaks. During this procedure, the load borne by the specimen and the elongation measured by the crosshead are measured.

[0252] Standard conditions:

[0253] Adjustment time: >96h at 50±2℃±10%rh

[0254] Test temperature: 23℃

[0255] Clamping distance: 100mm

[0256] Gauge length: 100mm

[0257] Secant modulus: 0.05%-0.25%

[0258] Test speed modulus: 1mm / min

[0259] Test speed: 200mm / min

[0260] Haze

[0261] Haze is measured according to ASTM D1003 test method (Method A - Hazemeter). This method covers the evaluation of specific light transmission and scattering properties of planar portions of materials, such as substantially transparent plastics.

[0262] The beam strikes the specimen and enters an integrating sphere. The interior of the sphere is uniformly coated with a matte white material to allow for diffusion. The detector in the sphere measures total transmittance, haze, and clarity (not part of ASTM D1003).

[0263] The incident light will be diffusely transmitted, changing the apparent quality of the product. This may be the result of scattering from the surface structure (roughness) or from within the particles, such as air inclusions, poorly dispersed pigments, dust inclusions or crystallization. As the roughness increases, the haze increases and the transmittance of the plastic decreases.

[0264] Standard conditions:

[0265] Adjustment time: >96h

[0266] Temperature: 23℃

[0267] Test Procedure: A-Haze Meter

[0268] Tear resistance (determined as Elmendorf tear (N) in machine direction (MD) and transverse direction (TD):

[0269] Tear resistance is measured according to ISO 6383-2 method. The force required to propagate a tear on a film sample is measured using a pendulum device and a constant radius specimen is used. The pendulum swings along an arc under the action of gravity, tearing the sample from the pre-cut slit. One side of the specimen is fixed by the pendulum and the other side is fixed by a fixed fixture.

[0270] The tear resistance is the force required to tear the sample. The relative tear resistance (N / mm) is then calculated by dividing the tear resistance by the thickness of the film.

[0271] Sealing start temperature (SIT); Sealing end temperature (SET), Sealing range

[0272] This method determines the sealing temperature range (sealing range) of polyethylene films, in particular blown films or cast films. The sealing temperature range is the temperature range over which the film can be sealed according to the conditions given below.

[0273] The lower limit (heat seal initiation temperature (SIT)) is the sealing temperature at which a seal strength of 5 N is achieved. The upper limit (seal end temperature (SET)) is achieved when the film sticks to the sealing device.

[0274] The measurements were performed according to a slightly modified ASTM F1921-12, where the test parameters sealing pressure, cooling time and test speed were modified. The force / temperature curve was continued until thermal failure of the film. The sealing range was determined on a 40 μm thick single-layer test blown film on a J&B Universal Sealer Model 4000, where the following additional parameters were used:

[0275] Adjustment time: >96h

[0276] Sample width: 25mm

[0277] Sealing pressure: 0.4N / mm 2 (PE)

[0278] Sealing time: 1 second

[0279] Delay time: 30 seconds

[0280] Sealing jaws size: 50x5 mm

[0281] Sealing jaws shape: flat

[0282] Sealing jaw coating: Niptef

[0283] Sealing temperature: ambient temperature -240℃

[0284] Sealing temperature interval: 5°C

[0285] Starting temperature: 50°C Clamp separation rate: 42 mm / s

[0286] Membrane sample preparation

[0287] Film samples were produced on a small-scale laboratory blown film line from COLLIN Lab&Pilot Solutions GmbH.

[0288] The line consisted of an extruder with a screw diameter of 25 mm and an aspect ratio of 30. The extruder temperature was set at 200 °C, the melt temperature was 202-204 °C and was recorded after 45 minutes of process stabilization. The extruder was followed by a blow molding head equipped with The die was annular and had a die gap of 1.5 mm. The line was run at a constant output of 6.5 kg / h and a line speed of 7.4 m / min. The blow-up ratio (BUR) of the film bubble was 2.5:1, resulting in a lay-flat width of 196 mm. The film thickness produced was 40 μm.

[0289] The produced membranes were used for the following mechanical tests.

[0290] Example:

[0291] Catalyst Example: Catalyst Preparation of CAT1:

[0292] SiO2 loading:

[0293] 10 kg of silica (PQ Corporation ES757, calcined at 600°C) was added from a feed bucket and inerted in the reactor until the O2 level reached less than 2 ppm.

[0294] Preparation of MAO / tol / MC:

[0295] At 25°C (oil circulation temperature) and 95rpm stirring, a 30wt% MAO toluene solution (14.1kg) was added from a balance to another reactor, followed by toluene (4.0kg). After adding toluene, the stirring speed was increased from 95rpm to>200rpm, with a stirring time of 30 minutes. Metallocene racemic-dimethylsilanediylbis{2-(5-(trimethylsilyl)furan-2-yl)-4,5-dimethylcyclopentadiene-1-yl}zirconium dichloride 477g was added from a metal cylinder, followed by 4kg toluene rinse (total toluene was 8.0kg). The reactor stirring speed was changed to 95rpm for MC feeding, returned to 200rpm and continued for 3h reaction time. After the reaction time, the MAO / tol / MC solution was transferred to a feed container.

[0296] Preparation of catalyst:

[0297] The reactor temperature was set to 10°C (oil circulation temperature) and stirring was adjusted to 40 rpm during the addition of MAO / tol / MC. MAO / tol / MC solution (22.2 kg) was added over 205 min, followed by a stirring time of 60 min (oil circulation temperature set to 25°C). After stirring, the "dry mix" was stabilized at 25°C (oil circulation temperature) for 12 h with a stirring speed of 0 rpm. The reactor was rotated 20° (back and forth) and stirred several times per hour at a speed of 5 rpm.

[0298] After stabilization, the catalyst was dried at 60°C (oil circulation temperature) for 2 h under a 2 kg / h nitrogen flow, followed by drying under vacuum for 13 h (same nitrogen flow rate, stirring at 5 rpm). The dried catalyst was sampled and the HC content was measured using a Sartorius moisture analyzer (model MA45) in a glove box using thermogravimetry. The target HC level was <2% (actual 1.3%).

[0299] polymerization:

[0300] The polymerization was carried out in a stirred autoclave with a volume of 20.9 L. The polymerization process is described as follows:

[0301] The evacuated autoclave was filled with 3600 g of propane. 0.5 mmol of triethylaluminium (0.62 mol / l heptane solution) was added using a stream of an additional 200 g of propane. The required batches of ethylene and hydrogen were added and the reactor was heated to the required prepolymerisation temperature of 60°C.

[0302] 400-600 mg of catalyst was weighed into a steel vial inside the glove box and suspended in 3 ml of heptane. The vial was then connected to the polymerization autoclave and the suspension was flushed into the reactor with 200 g of propane.

[0303] For the prepolymerization, the reactor was stirred at 60°C for 30-45 min. The pressure was kept constant at 21.1 bar by feeding ethylene with a flow meter. Subsequently, the temperature was raised to 85°C. The required batches of hydrogen and 1-butene were added to the reactor. At the same time, ethylene was added until the desired slurry polymerization pressure was reached.

[0304] For slurry polymerization, the reactor was stirred at 85° C. The pressure was kept constant by adding ethylene, 1-butene and hydrogen in fixed ratios. After the desired amount of ethylene was consumed, the reaction was stopped by venting and draining the reactor.

[0305] For gas phase polymerization, the reactor temperature was set to 75°C. The reactor was refilled with propane until the required inert gas pressure for gas phase polymerization was reached. Hydrogen and 1-hexene were then added to the reactor. At the same time, ethylene was added until the reactor pressure reached 20 bar. During the polymerization, the pressure was kept constant by feeding ethylene, 1-hexene and hydrogen at a fixed ratio. After the required amount of ethylene was consumed, the reaction was stopped by venting the reactor.

[0306] The detailed aggregation settings are shown in Table 1 below:

[0307] Table 1: Aggregation settings

[0308] Example CE1 CE2 IE1 IE2 catalyst CAT1 CAT1 CAT1 CAT1 Catalyst amount [mg] 600 600 400 400 Prepolymerization hydrogen batch [q] 0.005 0.005 0.030 0.030 Prepolymerized ethylene batch size [g] 64 64 52 52 Prepolymerization time [min] 45 45 45 30 Slurry hydrogen batch [g] 0.12 0.12 0.14 0.14 Slurry 1-butene batch [g] 14 14 0 0 Slurry pressure [bar] 39.8 39.8 39.9 39.9 Slurry hydrogen / ethylene feed ratio [g / g] 0.000076 0.000076 0.000068 0.000068 Slurry 1-butene / ethylene feed ratio [g / g] 0.008 0.008 0 0 Slurry ethylene consumption feed [g] 1000 950 700 550 Gas phase inert gas pressure [bar] 13 13 14.5 14.5 Gas phase hydrogen batch size [g] 0.017 0.028 0.022 0.025 Gas phase 1-hexene batch [g] 9 9 40 25 Gas phase hydrogen / ethylene feed ratio [g / g] 0.000043 0.000041 0.000036 0.000057 Gas phase 1-hexene / ethylene feed ratio [g / g] 0.066 0.066 0.156 0.112 Gas phase ethylene consumption feed [g] 1345 1279 912 762

[0309] The polymer was mixed with 0.027 wt% FX 5922 (BASF) and 0.24 wt% Irganox B 561 (BASF), compounded and extruded on a ZSK 18 twin screw extruder, where the wt% is relative to the total weight of the composition (total of mMDPE powder + additives = 100%). The melt temperature was ~195°C, the production rate was 2 kg / h for IE and 4 kg / h for CE1 / 2.

[0310] As comparative example 3 (CE3), the polymer of WO2008089978 of Example 1 was used.

[0311] The polymerization conditions are given in Table 1 of WO2008089978.

[0312] Table 2: Material properties of CE1 to CE3, IE1 and IE2

[0313]

[0314] nd Not detected

[0315] Single layer blown film

[0316] Table 3: Properties of blown films

[0317]

[0318] As can be seen from Table 3 above, the metallocene-catalyzed mMDPE-based films according to the present invention have improved mechanical properties (higher stiffness at the same dart drop impact strength (DDI) or higher dart drop impact strength (DDI) at the same stiffness) without deteriorating the sealing performance, and still have acceptable optical properties, especially haze.

[0319] The films of the invention show an optimal balance between stiffness, impact resistance and sealing properties. Furthermore, films based on mMDPE according to the invention have an improved relative tear resistance.

Claims

1. A metallocene-catalyzed multimodal medium density polyethylene (mMDPE) consisting of (i) 35.0 to 50.0 wt% of a polyethylene component (A) based on mMDPE, and (ii) 50.0 to 65.0 wt% of a polyethylene component (B) based on mMDPE, wherein the polyethylene polymer component (A) has 950 to 975 kg / m 3 Density in the range (ISO 1183), MFR2 in the range of 3.0 to 50.0 g / 10 min (190°C, 2.16 kg, ISO 1133); The polyethylene component (B) has 900 to 925 kg / m 3 Density in the range (ISO 1183), MFR2 in the range of 0.001 to 1.0 g / 10 min (190°C, 2.16 kg, ISO 1133); Among them, metallocene-catalyzed medium-density polyethylene (mMDPE) has 920 to 945 kg / m 3 Density in the range (ISO 1183), MFR2 (190°C, 2.16 kg, ISO 1133) in the range of 0.1 to 5.0 g / 10 min, and MFR in the range of 27 to 40 21 Ratio of MFR (190℃, 21.6kg, ISO 1133) to MFR2 (190℃, 2.16kg, ISO 1133) 21 / MFR2, and Molecular weight distribution (MWD) Mw / Mn (measured by GPC) in the range of 4.2 to 10.

0.

2. The metallocene-catalyzed multimodal medium density polyethylene (mMDPE) according to claim 1, wherein the mMDPE has one or two or all of the following: 922 to 940 kg / m 3 , preferably 923 to 935 kg / m 3 Density within the range (ISO1183), MFR2 (190°C, 2.16 kg, ISO 1133) in the range of 0.2 to 3.0 g / 10 min, preferably 0.3 to 2.5 g / 10 min, more preferably 0.4 to 2.0 g / 10 min, MFR in the range of 10.0 to 55.0 g / 10 min, preferably in the range of 12.0 to 50.0 g / 10 min, more preferably in the range of 15.0 to 45.0 g / 10 min 21 (190℃, 21.6kg, ISO 1133), and / or Flow rate ratio (FRR) MFR in the range of 28.0 to 38.0, preferably 29.0 to 35.0 21 / MFR2.

3. The metallocene-catalyzed multimodal medium density polyethylene (mMDPE) according to claim 1 or 2, wherein the mMDPE has A molecular weight distribution (MWD) Mw / Mn in the range of 4.2 to 8.0, preferably 4.8 to 6.5 and a weight average molecular weight Mw (measured by GPC) of at least 60,000 g / mol, preferably in the range of 70,000 to 130,000 g / mol, more preferably 75,000 to 125,000 g / mol, still more preferably 80,000 to 120,000 g / mol.

4. The metallocene-catalyzed multimodal medium density polyethylene (mMDPE) according to any one of the preceding claims 1 to 3, wherein in the mMDPE, the polyethylene component (A) is a polyethylene homopolymer and the polyethylene component (B) is a copolymer of ethylene and a C4 to C8 comonomer, preferably a C4 to C6 comonomer, more preferably a copolymer of ethylene and 1-hexene.

5. The metallocene-catalyzed multimodal medium density polyethylene (mMDPE) according to any one of the preceding claims 1 to 4, wherein in the mMDPE, The polyethylene component (A) has a molecular weight of 955 to 972 kg / m 3 , preferably 960 to 970 kg / m 3 , more preferably 962 to 968 kg / m 3 and a density (ISO 1183) in the range of 4.0 to 30.0 g / 10 min, preferably 5.0 to 20.0 g / 10 min, more preferably 6.0 to 15 g / 10 min., and The polyethylene component (B) has a molecular weight of 903 to 920 kg / m 3 , preferably 905 to 915 kg / m 3 , more preferably 905 to 912 kg / m 3 The preferred embodiment of the present invention has a density in the range of 0.05 to 1.0 g / 10 min, preferably 0.01 to 0.6 g / 10 min, more preferably 0.05 to 0.5 g / 10 min, and a density in the range of 0.05 to 1.0 g / 10 min (ISO 1183) and an MFR2 in the range of 0.005 to 0.8 g / 10 min, preferably 0.01 to 0.6 g / 10 min, more preferably 0.05 to 0.5 g / 10 min.

6. The metallocene-catalyzed multimodal medium density polyethylene (mMDPE) according to any one of the preceding claims 1 to 5, wherein the mMDPE has a total amount of C4 to C8 comonomers, preferably C4 to C6 comonomers, more preferably 1-hexene in the range of 1.5 to 5.0 mol%, preferably 1.6 to 4.0 mol%, more preferably 1.7 to 3.5 mol%, still more preferably 1.8 to 3.0 mol%, based on the mMDPE, and The total amount of C4 to C8 comonomers, preferably C4 to C6 comonomers in the polyethylene component (B) is in the range of 2.0 to 8.0 mol%, more preferably 2.5 to 7.0 mol%, even more preferably 3.0 to 6.0 mol%, still more preferably 3.2 to 5.5 mol%, based on the polyethylene component (B).

7. The metallocene-catalyzed multimodal medium density polyethylene (mMDPE) according to any one of the preceding claims, wherein the mMDPE is produced in the presence of a metallocene complex of formula (I): Wherein each X is independently a halogen atom, C 1-6 -alkyl, C 1-6 - alkoxy, phenyl or benzyl; Each Het is independently a monocyclic heteroaromatic group containing at least one heteroatom selected from O or S; L is -R'2Si-, wherein each R' is independently a C substituted with an alkoxy group having 1 to 10 carbon atoms. 1-20 -Hydrocarbon or C 1-10 -alkyl; M is Ti, Zr or Hf; Each R1 is the same or different, is C 1-6 -alkyl or C 1-6 - alkoxy; Each n is 1 to 2; Each R2 is the same or different, and is C 1-6 -alkyl, C 1-6 -alkoxy or -Si(R)3 group; Each R is optionally replaced by 1 to 3 C 1-6 -alkyl substituted C 1-10 - alkyl or phenyl; and Each p is from 0 to 1.

8. A film comprising the metallocene-catalyzed multimodal medium density polyethylene (mMDPE) according to any one of the preceding claims 1 to 7.

9. The film according to claim 8, wherein the film comprises at least 50 wt%, more preferably at least 60 wt%, even more preferably at least 70 wt%, still more preferably at least 80 wt% of the metallocene-catalyzed mMDPE according to any one of the preceding claims 1 to 7, based on the total weight of the film, most preferably the film consists of the metallocene-catalyzed mMDPE.

10. The film according to claim 8 or 9, wherein the film a) a tensile modulus (measured on a 40 μm monolayer test blown film according to ISO 527-3) in the machine direction (MD) in the range of 350 MPa to 800 MPa, preferably 380 MPa to 500 MPa and in the transverse direction (TD) in the range of 400 MPa to 800 MPa, preferably 420 MPa to 550 MPa, and b) a dart drop impact strength (DDI) of at least 150 g to at most 500 g, preferably 200 g to at most 450 g, more preferably 220 g to at most 400 g, measured on a 40 μm single layer test blown film according to ISO 7765-1:1988, and c) according to formula (I): Relationship between mechanical properties and sealing properties determined on 40 μm test blown films, wherein the tensile modulus in the longitudinal direction is measured on 40 μm test blown films at 23°C according to ISO 527-3, DDI is the dart impact strength determined on 40 μm test blown films according to ISO 7765-1:1988, and SIT is the seal initiation temperature measured on 40 μm test blown films as described in the experimental part.

11. The film according to claim 8 or 9, wherein the film a) a tensile modulus (measured on a 40 μm monolayer test blown film according to ISO 527-3) in the machine direction (MD) in the range of 200 MPa to 600 MPa, preferably 250 MPa to 400 MPa and in the transverse direction (TD) in the range of 250 MPa to 600 MPa, preferably 300 MPa to 500 MPa, and b) a dart drop impact strength (DDI) of at least 700 g to at most 2000 g, preferably 800 g to at most 1600 g, more preferably 900 g to at most 1400 g, measured on a 40 μm single layer test blown film according to ISO 7765-1:1988, and c) according to formula (I): Relationship between mechanical properties and sealing properties determined on 40 μm test blown films, wherein the tensile modulus in the longitudinal direction is measured on 40 μm test blown films at 23°C according to ISO 527-3, DDI is the dart impact strength determined on 40 μm test blown films according to ISO 7765-1:1988, and SIT is the seal initiation temperature measured on 40 μm test blown films as described in the experimental part.

12. The film according to any one of the preceding claims 8 to 11, wherein the film has a haze measured on a 40 μm test blown film according to ASTM D1003 of less than 35%, preferably in the range of 5 to 32%, more preferably in the range of 10 to 30%, even more preferably in the range of 10 to 20% or 21 to 30%.

13. The film according to any one of the preceding claims 8 to 12, wherein the film has a relative Elmendorf tear resistance in the machine direction (MD) of at least 60 N / mm to at most 300 N / mm, preferably 70 N / mm to at most 250 N / mm, more preferably 80 N / mm to at most 220 N / mm, measured according to ISO 6383 / 2 on a blown film with a film thickness of 40 μm, and In the transverse direction (TD) it is at least 140 N / mm to at most 350 N / mm, preferably 150 N / mm to at most 300 N / mm, more preferably 170 N / mm to at most 250 N / mm.

14. Use of the film according to any of the preceding claims 8 to 13 in packaging applications or as a layer in a multilayer polyethylene-based blown film, preferably as a core layer in a multilayer polyethylene-based blown film.

Citation Information

Patent Citations

  • Apparatus and method for producing ethylene polymer

    EP0479186A2

  • High solids slurry polymerization

    EP0891990A2

  • Polymerisation reactor

    EP1310295A1

  • Process and apparatus for producing olefin polymers

    EP1415999A1

  • Process for producing polyethylene

    EP1591460A1